On the Bus with Bill Monroe : My Five-Year Ride with the Father of Blue Grass - Hembree, Mark, 1955- (Book collections on Project MUSE., 2022)
"An impromptu rehearsal led Mark Hembree into a five-year stint (1979-1984) as the bassist for Bill Monroe's Blue Grass Boys. Hembree's journey included playing at the White House and on the acclaimed album Master of Bluegrass. But it also put him on a collision course with the rigors of touring, the mysteries of Southern culture, and the complex personality of bandleader-legend Bill Monroe. Whether it's figuring out the best time for breakfast (early) or for beating the boss at poker (never), Hembree gives fans an up-close look at the unglamorous life of a touring musician in the sometimes baffling, always colorful company of a bluegrass icon. The charming story of a Yankee fish out of water, On the Bus with Bill Monroe mixes memoir with storytelling to recount the adventures of a Northerner learning new songs and new ways"--